A statistical method to establish voltage dependency load parameters based on field measurements - Tang J.H.; Au M.T.; Busrah A.M.; Anthony T.M. (Warsaw University of Technology, 2023)
Voltage dependency static load models are commonly applied to simulation studies on low voltage network. However, there is generally a lack of established key parameters for voltage dependency static load models to represent loads commonly used in residential premises. This paper presents a statistical approach to determine key parameters in voltage dependency static load models. Eleven (11) individual single- phase types of loads were investigated based on field measurements corresponding to on-load tap-changer operations at 33 kV upstream. Changes in active and reactive power of the individual loads due to changes in input voltages were recorded and analyzed statistically to determine the parameters used for the voltage dependency static load model. The results were validated through laboratory measurements of the individual loads and found to be consistent and in close agreement with results obtained from the statistical analysis. A simulation case study performed on a low voltage network with solar photovoltaic penetration indicates significant deviation in peak power demand, power losses, reverse power flow and energy consumption in the network between constant power load model and LTV model in particular when source voltage is set at above 1.0 per unit. 2018 Int. J. Elec. & Elecn. Eng. & Telcomm.